2018
DOI: 10.14393/bj-v34n2a2018-39074
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of psycho-emotional constructs and self-management in health of patients with cancer

Abstract: The present study aimed measure self-esteem, anxiety and depression and activation scores in individuals with cancer; compare these scores according to whether or not chemotherapy was performed and verify the influence of these constructs in the self-management in health. This study is a Cross-sectional study with a quantitative approach, performed at the outpatient clinic of a school hospital. The instrument was answered by adult patients, diagnosed with cancer for at least 6 months and in outpatient follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the study (SOUZA et al, 2018), only depression, in the HADS subscale, showed a statistical difference between the means, regarding gender and age group (p<0.05).…”
Section: Harmony Of Knowledge Exploring Interdisciplinary Synergiesmentioning
confidence: 71%
See 2 more Smart Citations
“…In the study (SOUZA et al, 2018), only depression, in the HADS subscale, showed a statistical difference between the means, regarding gender and age group (p<0.05).…”
Section: Harmony Of Knowledge Exploring Interdisciplinary Synergiesmentioning
confidence: 71%
“…In the study by Souza et al (2018) (SOUZA et al, 2018 the scores to measure symptoms of anxiety and depression showed that these symptoms are at normal levels, equivalent to the levels of the general population. This result may be related to the high levels of self-esteem shown in the study in question.…”
Section: About the Article Bymentioning
confidence: 97%
See 1 more Smart Citation
“…In a study by Souza et al (2018) focusing on cancer patients, there was no statistically significant correlation between the variable time since diagnosis and depression, anxiety, self-esteem and activation symptoms, except when the correlation was made with the variables level of schooling and number of comorbidities. This information may contribute to other studies involving the variable: time of diagnosis for cancer patients.…”
Section: Discussionmentioning
confidence: 92%